Schizotypy is associated with difficulty maintaining multiple hypotheses. Issue 7 (July 2021) - Griffiths, Oren; Balzan, Ryan
Among neurocognitive accounts of delusions, there is a growing consensus that it is the certainty with which delusions are held, rather than their content that defines some beliefs as delusional. On a continuum model of psychosis, this inappropriate certainty ought to be present (albeit in an attenuated form) in healthy adults who score highly in schizotypy. It was hypothesised that this might be most evident in circumstances where the environment provides incomplete or probabilistic information, which thereby forces the participant to hold two imperfectly supported, concurrent hypotheses in mind. A cued visual search task was used to measure people's capacity to use partially predictive information (i.e., a cue that predicted the target may occur in one of the two locations) to facilitate speeded responding. As hypothesised, people's performance on the trials that required holding two hypotheses in mind concurrently was significantly and specifically associated with the positive components of schizotypy. This finding is consistent with a hyperfocusing of attention in schizophrenia, and may help explain why delusion-prone individuals have a tendency to "jump to conclusions" or be resistant to disconfirming information when faced with multiple, partially supported hypotheses.